Characterization of users at risk of developing diabetes: a cross-sectional study - Carla Lidiane Jácome de Lima; Thalys Maynnard Costa Ferreira; Patrícia Simplício de Oliveira; Josefa Danielma Lopes Ferreira; Eliane Cristina da Silva; Marta Miriam Lopes Costa
ABSTRACT Objective: To characterize the profile of users at risk of developing diabetes mellitus type 2 according to sociodemographic and clinical variables. Method: Cross-sectional study, descriptive, quantitative approach conducted with 266 users of Basic Care. Inferential statistics analysis, calculating the crude prevalence ratio with confidence interval of 95% and Kruskal-Wallis test, and application of the multivariate technique simple Correspondence Analysis. Results: It was noted that 83.1% were women and 36.4% frequented the Family Health Unit from 1 to 5 years. Regarding the factors associated with diabetes mellitus type 2, 66.5% of the users were overweight and 77.9% were rated with central obesity. The great majority, 77.4%, did not practice physical activities and 21.1% had altered glycemia. Conclusion: The results showed that many risk factors for developing diabetes mellitus type 2 were among the population of the study.